Implementasi Rigging pada Rambut 3D - Askar, Muhammad Ichfan; Setyanto, Arief; Sofyan, Amir Fatah (Inspiration: Jurnal Teknologi Informasi dan Komunikasi, 2021)
3D animation is an art to be able to create and move 3D objects, so that it can produce amovement in accordance with the wishes of the maker. In making the animation, 3D objet andrigging are needed. The stages of program implementation are: The first stage is an object,where 3D objects choose several types, one of which is always used is a human object. Humanobjects have a high level of difficulty, especially the hair. Each hairdo making chooses adifferent surgical process. The second stage is rigging, regular rigging is likened to ananimation bone that functions to move an animation object. Based on this, this researchdescribes the process of implementing rigging in several 3D hairstyles and basic patterns todetermine the type of hair to be made. The implementation of this model uses a rigging modelapproach between the object and the animator so that it can produce 3D animation works well.